2013
DOI: 10.1021/nn401661d
|View full text |Cite
|
Sign up to set email alerts
|

Ultrarapid Generation of Femtoliter Microfluidic Droplets for Single-Molecule-Counting Immunoassays

Abstract: We report a microfluidic droplet-based approach enabling the measurement of chemical reactions of individual enzyme molecules and its application to a single-molecule-counting immunoassay. A microfluidic device is used to generate and manipulate <10 fL droplets at rates of up to 1.3 × 10(6) per second, about 2 orders of magnitude faster than has previously been reported. The femtodroplets produced with this device can be used to encapsulate single biomolecular complexes tagged with a reporter enzyme; their sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
204
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(207 citation statements)
references
References 39 publications
2
204
0
1
Order By: Relevance
“…Theoretically, the rate-limiting step for the application of this platform is the FACS-assisted droplet-screening technology (20), which is limited to several tens of thousands of events per second. The characteristics of the MDE-FACS platform-specifically, sensitive detection combined with specific separation-allow its use in practical research on drug design, including the selection of novel desired activity, direct isolation of probiotics, antibiotic producers, and prediction of unculturable effectors.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, the rate-limiting step for the application of this platform is the FACS-assisted droplet-screening technology (20), which is limited to several tens of thousands of events per second. The characteristics of the MDE-FACS platform-specifically, sensitive detection combined with specific separation-allow its use in practical research on drug design, including the selection of novel desired activity, direct isolation of probiotics, antibiotic producers, and prediction of unculturable effectors.…”
Section: Discussionmentioning
confidence: 99%
“…10 Improvements in sensitivity could be possible by adapting single-molecule detection techniques [37][38][39][40] or through the implementation of amplification schemes. More generally, we have shown that our microfluidic MITOMI platform 9,41-43 is capable of measuring protein biomarkers in hundreds to thousands of samples with highsensitivity and high dynamic-range.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, great effort has been spent on creating uniform reactors, including fabricated microarrays [20][21][22][23][24][25] and microfluidic droplets, [26][27][28] in a high throughput manner for single enzyme analysis. Compared with a microarray, microdroplets have the advantages of ultrahigh throughput, low cost, flexible manipulation, and low non-specific adsorption to channel/ chamber wall by oil phase isolation, offering attractive alternative reactors for protein quantification.…”
Section: Introductionmentioning
confidence: 99%
“…For example, very recently, Shim et al fabricated a microfluidic device capable of generating and trapping 200 000 highly uniform femtoliter droplets for the measurement of chemical reactions of single-enzyme molecules and the application to a single-molecule-counting immunoassay. 26 Takeuchi et al developed a method that utilizes an immiscible liquid phase to instantly enclose thousands of uniform femtoliter droplets within microchambers built in microchannel walls to study enzymatic activities at single-molecule levels. 27 In these two examples, droplets were stably trapped for imaging analysis, with the former relying on a complicated valve and post design and the latter using a non-scalable microchamber format.…”
Section: Introductionmentioning
confidence: 99%